1992
DOI: 10.1002/ajmg.1320420408
|View full text |Cite
|
Sign up to set email alerts
|

Amplification of ten deletion‐rich exons of the dystrophin gene by polymerase chain reaction shows deletions in 36 of 90 Japanese families with Duchenne muscular dystrophy

Abstract: We analyzed DNA samples taken from 95 Duchenne muscular dystrophy (DMD) patients belonging to 90 different families in Japan using the polymerase chain reaction. Ten different regions at the 5' end or in the central region of the dystrophin cDNA gene that were previously shown to be prone to deletion were selected for amplification and analysis. Patients in 36 of the 90 families (40%) had deletions in at least one of these segments of the gene. Identical deletions were detected in the dystrophin gene of patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

1993
1993
2007
2007

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 14 publications
1
6
0
Order By: Relevance
“…In this study, deletion breakpoints were located mainly in introns 44 (30%), 45 (30%) and 50 (37%). Several authors have previously shown that intron 44 is the most frequent site for rearrangements in the DMD gene [Den Dunnen et al, 1989;Upadhyaya et al, 1990;Kitoh et al, 1992], whereas in the Greek population, as in our population, a major ''hot spot'' was located in intron 50 [Florentin et al, 1995]. lanes 1 and 2) and exons 45/46/52 (lanes 3 and 4).…”
Section: Discussionsupporting
confidence: 43%
“…In this study, deletion breakpoints were located mainly in introns 44 (30%), 45 (30%) and 50 (37%). Several authors have previously shown that intron 44 is the most frequent site for rearrangements in the DMD gene [Den Dunnen et al, 1989;Upadhyaya et al, 1990;Kitoh et al, 1992], whereas in the Greek population, as in our population, a major ''hot spot'' was located in intron 50 [Florentin et al, 1995]. lanes 1 and 2) and exons 45/46/52 (lanes 3 and 4).…”
Section: Discussionsupporting
confidence: 43%
“…We have previously screened for deletion mutations in the dystrophin gene by using PCR (13,16). Nine exons distributed throughout the deletion-prone region of the dystrophin gene have been amplified from genomic DNA from over 200 Japanese patients with DMD/BMD.…”
Section: Resultsmentioning
confidence: 99%
“…Kitoh et al [10] studied 99 Japanese patients with DMD and found deletions in 40% of patients. In the West Midlands region of Britain, Roddie and Bundey [11] reported that DMD was twice as common as expected in Indians and less common than expected in Pakistanis.…”
Section: Discussionmentioning
confidence: 99%